Effects of microencapsulated plant essential oils on growth performance, immunity, and intestinal health of weaned Tibetan piglets - Chen, Xiaolian; Song, Wenjing; Xiong, Pingwen; Cheng, Di; Wei, Weiqun; Zhou, Quanyong; Xu, Chuanhui; Song, Qiongli; Ji, Huayuan; Hu, Yan; Zou, Zhiheng (Frontiers in Veterinary Science, 2024)
IntroductionPlant essential oils (PEOs) have received significant attention in animal production due to their diverse beneficial properties and hold potential to alleviate weaning stress. However, PEOs effectiveness is often compromised by volatility and degradation. Microencapsulation can enhance the stability and control release rate of essential oils. Whether different microencapsulation techniques affect the effectiveness remain unknown. This study aimed to investigate the effects of PEOs coated by different microencapsulation techniques on growth performance, immunity, and intestinal health of weaned Tibetan piglets.MethodsA total of 120 Tibetan piglets, aged 30 days, were randomly divided into five groups with four replicates, each containing six piglets. The experimental period lasted for 32 days. The groups were fed different diets: a basal diet without antibiotics (NC), a basal diet supplemented with 10 mg/kg tylosin and 50 mg/kg colistin sulfate (PC), 300 mg/kg solidified PEO particles (SPEO), 300 mg/kg cold spray-coated PEO (CSPEO), or 300 mg/kg hot spray-coated PEO (HSPEO).ResultsThe results showed that supplementation with SPEO, CSPEO, or HSPEO led to a notable decrease in diarrhea incidence and feed to gain ratio, as well as duodenum lipopolysaccharide content, while simultaneously increase in average daily gain, interleukin-10 (IL-10) levels and the abundance of ileum Bifidobacterium compared with the NC group (p < 0.05). Supplementation with SPEO, CSPEO, or HSPEO significantly elevated serum immunoglobulin G (IgG) levels and concurrently reduced serum lipopolysaccharide and interferon γ levels compared with the NC and PC groups (p < 0.05). Serum insulin-like growth factor 1 (IGF-1) levels in the SPEO and HSPEO groups significantly increased compared with the NC group (p < 0.05). Additionally, CSPEO and HSPEO significantly reduced jejunum pH value (p < 0.05) compared with the NC and PC groups (p<0.05). Additionally, Supplementation with HSPEO significantly elevated levels of serum immunoglobulin M (IgM) and interleukin-4 (IL-4), abundance of ileum Lactobacillus, along with decreased serum interleukin-1 beta (IL-1β) levels compared with both the NC and PC groups.DiscussionOur findings suggest that different microencapsulation techniques affect the effectiveness. Dietary supplemented with PEOs, especially HSPEO, increased growth performance, improved immune function, and optimized gut microbiota composition of weaned piglets, making it a promising feed additive in piglet production.